2019
DOI: 10.1177/1747493019828554
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of carotid free-floating thrombus: A systematic literature review

Abstract: Background: There is no consensus regarding the management of carotid free-floating thrombi in patients with acute ischemic stroke and transient ischemic attack. Aims: This systematic review aims to (1) describe the current imaging methods for diagnosis of carotid free-floating thrombi and its associated risk factors, (2) estimate the proportion of carotid free-floating thrombi diagnosed in stroke patients, (3) estimate the proportion of carotid free-floating thrombi patients treated medically and surgically, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
65
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 27 publications
4
65
0
2
Order By: Relevance
“…From a medical perspective the principle treatment options consist of anti-coagulation, anti-platelet therapy or thrombolysis. In the recent systematic literature review of Fridman et al [10]. The primary endpoint in this analysis was a composite of any stroke, transient ischemic attack (TIA), silent brain ischemia on diffusion-weighted MRI scan, or death at 30 days after the index event.…”
Section: Discussionmentioning
confidence: 99%
“…From a medical perspective the principle treatment options consist of anti-coagulation, anti-platelet therapy or thrombolysis. In the recent systematic literature review of Fridman et al [10]. The primary endpoint in this analysis was a composite of any stroke, transient ischemic attack (TIA), silent brain ischemia on diffusion-weighted MRI scan, or death at 30 days after the index event.…”
Section: Discussionmentioning
confidence: 99%
“…FFT constitute a rare, but known, cause of cerebral ischemia. The prevalence of FFT is described at about 1.5% to 1.6% in stroke or transient ischemic attack (TIA) patients . Carotid artery ultrasonography is not only of importance for a first diagnosis, but furthermore provides an ideal monitoring method .…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of FFT is described at about 1.5% to 1.6% in stroke or transient ischemic attack (TIA) patients . Carotid artery ultrasonography is not only of importance for a first diagnosis, but furthermore provides an ideal monitoring method . Regarding the prognosis, Fridman et al found a 17.1% risk of TIA, silent brain ischemia, stroke, or death in a 30‐day follow‐up of patients admitted to hospital for acute ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations